Problematika Penyusunan Perencanaan Pembelajaran di Madrasah - Nur, Muhammad (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This study tried to find the problems in teaching plan of Madrasah. The research method used is descriptive qualitative. The researcher collected the data by using observation, interview, and documentation. The data analysis technique, which was used, is the data analysis of interactive model proposed by Miles and Hubberman. The result of the study shows that: firstly, the problems in teaching plan of Madrasah are technical and non technical problems. They are some technical problems, such as: the lack of teachers’ knowledge in planning the lesson, the difficulty in determining the appropriate lesson, the difficulty in choosing the appropriate teaching methods, the difficulty in choosing the teaching media, and the difficulty in achieving the target of teaching and learning. Whereas, the non technical problems are the duration of teaching, multiple teaching subject, and additional jobs for the teacher. Secondly, the efforts to solve the problems are: maximizing the time of teaching, academic guidance, and the use of various teaching method and media.